Migratory connections of Coraciiformes of Kazakhstan based on bird ringing - AIZHAN E. TASHIMOVA; ANDREY E. GAVRILOV; YEKATERINA E.V. AKENTYEVA; YELENA SERGEEVNA CHALIKOVA; ZARIPOVA K.H. SYRYMGUL; SAIDINA S. KOBEGENOVA; BEKZHAN T. BERDIKULOV (Society for Indonesian Biodiversity, 2025)
Abstract. Tashimova AR, Gavrilov E, Akentyeva YEV, Chalikova YS, Syrymgul ZK, Kobegenova SS, Berdikulov BT. 2025. Migratory connections of Coraciiformes of Kazakhstan based on bird ringing. Biodiversitas 26: 4706-4713. This study provides the first long-term and comprehensive analysis of bird ringing data for four Coraciiformes species, Eurasian Roller (Coracias garrulus), Common Kingfisher (Alcedo atthis), European Bee-eater (Merops apiaster), and Blue-cheeked Bee-eater (M. persicus), captured in Kazakhstan between 1966 and 2025, with most data obtained from Shakpak Pass, a major migratory bottleneck in Central Asia. Over these 60 years, more than 26,000 individuals were ringed, yet only 35 recoveries were reported, highlighting the scarcity of long-distance encounter data in the region. The majority of recoveries involved M. apiaster, which demonstrated extensive migratory connectivity, including southward movements through Uzbekistan and Kyrgyzstan, westward passage toward the Caspian region, and remarkable long-distance encounters from Saudi Arabia, Syria, and even France. The latter represents a case of abmigration, providing evidence of population mixing between Central Asia and Europe. By contrast, C. garrulus and M. persicus were mainly documented as consistent passage migrants through Shakpak Pass, while A. atthis displayed signs of philopatry at local ringing sites. These findings emphasize the importance of Central Asia as a critical, yet understudied, segment of Eurasian migration systems. The exceptionally low recovery rates stress the urgent need to combine traditional ringing with modern tracking tools and to enhance public awareness and reporting to strengthen migration research and conservation.